A cost-effective retrofit of conventional distillation sequence to dividing-wall prefractionator configuration. (2nd February 2018) - Minh, Le Quang; Pham, Tram Ngoc; Long, Nguyen Van Duc; Shin, Joonho; Lee, Moonyong
Graphical abstract: Highlights: A dividing wall prefractionator configuration (DWPC) was studied for safe and cost-effective retrofit. A combined optimization method was proposed and applied for reliable design and fair comparison. Practical guideline was developed for the potential retrofit of DWPC. The performance of proposed DWPC was illustrated through several industrial cases. Abstract: A dividing-wall prefractionator configuration was investigated for a safe and economic retrofit of the conventional sequence using simple distillation columns. In the proposed retrofit configuration, the first column was modified to a dividing wall column as a prefractionator to supply prefractionated multi-feeds to the subsequent column. To investigate the effectiveness of the proposed configuration, nine near-ideal feed mixtures were considered for analysis. The proposed configuration was then compared with several other alternative configurations. The proposed dividing-wall prefractionator efficiently generates prefractionated multi-feed streams avoiding feed mismatch and remixing effect with low modification cost. Moreover, because the proposed retrofit configuration allows for flexible switching between the dividing-wall prefractionator and the conventional operating mode, a safe retrofit is also ensured by reducing the operational risks. Several industrial retrofit cases were studied to validate the proposed dividing-wall prefractionator configuration.